2020
DOI: 10.3390/w12020457
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hyporheic Exchange on Macroinvertebrate Community in the Weihe River Basin, China

Abstract: The effect of hyporheic exchange on macroinvertebrates is a significant topic in ecohydraulics. A field study was conducted during May and June 2017 to investigate the impacts of magnitude and patterns of hyporheic exchange on the sediment macroinvertebrate community in the Weihe River basin. The results demonstrate that upwelling flows cause resuspension of riverbed sediment, increasing the proportion of swimmer groups (such as Baetidae) in the macroinvertebrate community. However, large resuspension of river… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 89 publications
1
8
0
Order By: Relevance
“…Second, we also revealed that HWE in the examined low dynamic, temperate, perennial lowland river cannot be considered a factor to explain distributions, spatial patterns and composition of bottom-dwelling macroinvertebrates better than the other environmental variables, such as river depths, flow velocities and cross-section's area, which confirmed to a certain extent the conclusions of Monk et al (2006). Although statistical significance in different indicators of BMI abundances and compositions analysed in our study was not found, observed relationships remained similar to the ones Ling et al (2020) provided: infiltrating conditions, where river waters penetrate hyporheic zone in a downwelling flux, prerequisited more suitable conditions for BMI persistence than the conditions of groundwater exfiltration (upwelling flux in a hyporheic zone). They also observed that hyporheic upwelling flows, representing the river's draining conditions, caused resuspension of finer sediments and increased the proportion of swimmers in total abundance of BMI.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Second, we also revealed that HWE in the examined low dynamic, temperate, perennial lowland river cannot be considered a factor to explain distributions, spatial patterns and composition of bottom-dwelling macroinvertebrates better than the other environmental variables, such as river depths, flow velocities and cross-section's area, which confirmed to a certain extent the conclusions of Monk et al (2006). Although statistical significance in different indicators of BMI abundances and compositions analysed in our study was not found, observed relationships remained similar to the ones Ling et al (2020) provided: infiltrating conditions, where river waters penetrate hyporheic zone in a downwelling flux, prerequisited more suitable conditions for BMI persistence than the conditions of groundwater exfiltration (upwelling flux in a hyporheic zone). They also observed that hyporheic upwelling flows, representing the river's draining conditions, caused resuspension of finer sediments and increased the proportion of swimmers in total abundance of BMI.…”
Section: Discussionsupporting
confidence: 75%
“…The first steps towards evaluating the influence of hyporheic water exchange (HWE) on BMI in different scales provided interesting results. Ling et al (2020) observed that hyporheic upwelling flows, representing the river's draining conditions cause resuspension of finer sediments and increase the proportion of swimmers (in their case, Baetidae) in total abundance of BMI. They also observed that downwelling flows (representing conditions of river infiltration to the aquifer through the hyporheic zone) produced richer compositions and abundances of BMI than the upwelling ones.…”
Section: Introductionmentioning
confidence: 99%
“…Water flux obtained by the conservative-solute transport model before and after the introduction of invertebrate showed that the presence of tubificids significantly increased the proportion of mobile region, indicating modified water flux [24]. Research has also shown that the macroinvertebrate community may be related to the magnitude and patterns of water exchange [25]. The presence of tubificid worms can effectively enhance the water flux while the chironomid larvae failed to show the similar effects, which indicated that the influence depends on the mode of the bioturbation [15,26].In addition, macroinvertebrate activity may alter flow paths in the interstitial spaces [27].…”
Section: Introductionmentioning
confidence: 99%
“…Four studies approached the stream and river systems from a variety of perspectives, ranging from the physical modelling of flow with vegetation [13] and the numerical simulation of solute transport in river with dead zones [14], to the laboratory study of flood discharge atomisation [15] and the geomorphic characterisation and classification of a large river [16]. Three contributions are about hyporheic fluxes: two field studies investigated these fluxes at a small river confluence [17] and the effects of such fluxes on the macroinvertebrate community [18], while their relationship with the bioturbation activity of macroinvertebrates was studied in laboratory [19]. The last two articles addressed the accuracy of groundwater flux measurement using a seepage meter in the laboratory [20] and the experimental validation of the Darcy-Buckingham (DB) law in unsaturated porous rocks [21].…”
mentioning
confidence: 99%
“…Hyporheic exchange affects the substrate properties and water quality and thus the habitat availability and suitability of macroinvertebrate community in river ecosystems. In this context, Lin et al [18] conducted a field study to explore the impacts of magnitude and pattern (upwelling and downwelling) of hyporheic exchange on the sediment macroinvertebrate community in the Weihe River Basin in Shaanxi, China. The results showed that while upwelling flows caused the resuspension of riverbed sediment and increased the proportion of swimmer groups in the macroinvertebrate community, downwelling is more likely to produce abundant and rich invertebrate communities.…”
mentioning
confidence: 99%